2019
DOI: 10.1016/j.jvscit.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-power diode laser at 1060 nm for the treatment of vascular lesions

Abstract: The use of 1060-nm wavelength light emitted from a high-power diode laser is a novel method for the removal of vascular lesions. Two Caucasian women with Fitzpatrick skin phototype II, who had various vascular lesions, were treated with a 1060-nm high-power diode laser, applying a fluence of 120 J/cm2 and a single pulse duration of 74 milliseconds. Immediate results were that the cherry angiomas became dark and a scab was formed (that remitted 2 weeks after treatment); the telangiectasias and venulectasias dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been reported that while the Nd:YAG laser shows a high therapeutic effect, the diode laser of the same wavelength is cheaper than the Nd:YAG laser with reduced cost and high efficiency. 5,6 Although the length of a diode laser coherence is shorter than that of a Nd:YAG laser coherence, much absorption occurs from the outer skin, thus limiting the transmission depth of light energy. Due to such restriction, many patients complain of fever on the surface of the skin during a high-power treatment with a diode laser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that while the Nd:YAG laser shows a high therapeutic effect, the diode laser of the same wavelength is cheaper than the Nd:YAG laser with reduced cost and high efficiency. 5,6 Although the length of a diode laser coherence is shorter than that of a Nd:YAG laser coherence, much absorption occurs from the outer skin, thus limiting the transmission depth of light energy. Due to such restriction, many patients complain of fever on the surface of the skin during a high-power treatment with a diode laser.…”
Section: Introductionmentioning
confidence: 99%
“…Due to such restriction, many patients complain of fever on the surface of the skin during a high-power treatment with a diode laser. [1][2][3][4][5][6] To solve such problem, the objecteive of this study was to determine whether the treatment efficiency of a diode laser could be improved by using an optical clearing agent (OCA). Research is being actively conducted to transmit light deeply to living tissues in treatment using a laser.…”
Section: Introductionmentioning
confidence: 99%
“…Usually asymptomatic, cherry angiomas can potentially become a certain reason for concern from a cosmetic point of view. Several therapeutic approaches have been suggested including light-based devices such as Nd:YAG laser, intense pulsed light, and pulsed dye laser, as well as other non-laser options including sclerotherapy, cryotherapy, or electrotherapy [ 104 , 107 , 108 ]. Even though acromegaly represents an infrequent part of MEN1, with a penetrance of 10% due to its severe impact, the diagnosis of such skin findings should not be overlooked [ 1 , 109 , 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%